Advanced Computational Methods for Knowledge Engineering Proceedings of 3rd International Conference on Computer Science, Applied Mathematics and Applications - ICCSAMA 2015 - Le Thi, Hoai An; Nguyen, Ngoc Thanh; Do, Tien Van (Advances in Intelligent Systems and Computing,, 2015)
This volume contains the extended versions of papers presented at the 3rd International Conference on Computer Science, Applied Mathematics and Applications (ICCSAMA 2015) held on 11-13 May, 2015 in Metz, France. The book contains 5 parts: 1. Mathematical programming and optimization: theory, methods and software, Operational research and decision making, Machine learning, data security, and bioinformatics, Knowledge information system, Software engineering. All chapters in the book discuss theoretical and algorithmic as well as practical issues connected with computation methods & optimization methods for knowledge engineering and machine learning techniques.  .